The Practicality and Effectiveness of Poetry Text Learning Kit in E-Learning - Wisudariani, Made Rai; Wiraningsih, Putu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Curriculum and the pandemic require teachers to teach poetry text using e-learning kits that allow the use of technology. Virtual face-to-face Learning kits prepared by teachers must be reconstructed according to the conditions of students in e-learning. However, practical and effective learning kit needs to be studied further. Thus, this study aimed at developing an e-learning oriented poetry text learning kit that was practical and effective in Indonesian language learning. The subjects of this study were teachers and the tenth-grade students. Observation, questionnaire, and test methods were used to obtain data. The results by the teacher and students showed that the learning kit made was very practical. Effective learning kits are used in learning. There is a significant difference between learning outcomes in the experimental and control groups. The average value of the experimental class was 83, which was higher than the control class, which only reached an average grade of 74. The poetry text learning kit was oriented towards practical e-learning strategies and is effectively used in learning as an alternative to online learning.